Fail Fast, Fix Faster: Risk-Based Testing for Agile Product Teams (Global Journals of Research in Engineering, 2025)
Efficient and effective testing strategies are critical within agile product development Traditional testing approaches often fall short in fast-paced agile environments leading to delayed feedback and increased time-to-market A proposed methodology Risk-Based Testing RBT tailored for agile teams prioritizes testing efforts based on the likelihood and impact of potential risks By integrating RBT into the agile workflow the feedback loop is accelerated enabling teams to fail fast and fix faster The efficacy of this approach is demonstrated through case studies and simulated agile sprints showcasing a significant reduction in critical defects and improved release velocity Practical implications of implementing RBT are discussed highlighting its potential to enhance product quality and accelerate development cycles Results indicate a substantial improvement in agile testing practices paving the way for more responsive and resilient product development A novel perspective on agile testing is offered by providing a structured framework for prioritizing testing efforts based on risk assessments thereby improving overall product quality and release speed
Keywords: agile testing; risk-based testing; agile product development; test prioritization; defect management; continuous integration; continuous delivery